Developing a new package program for manufacturing plastic injection moldings and cost calculation - Ozekm, Cebeli; Celik, Yahya Hisman (My University, 2009)
In this study, a program has been developed to calculate molding manufacturing cost of plastic products manufactured by the techniques of plastic injection molding. Delphi programming language has been used in the development of the program. Separate data entries for the parameters affecting the mold cost such as materials from which the mold will be manufactured, the properties of injection molding machines, plastic material types, standard mold components, and geometric properties of the plastic product to be manufactured has been formed. The program makes calculation about optimum how many sections the mold will consist of and how much molding dimensions will be according to these parameter values. According to information obtained from the program, the sum of mold raw material costs, design costs, and labor and processing costs is calculated as total mold cost. To check the effectiveness of the program, an experimental study has been conducted to calculate the costs of plastic thread elbow component used in installation works. While the SolidWorks has been used for mold design, the Mastercam program has been used in determining the processing time. The effectiveness of the program has been checked by comparing the results obtained from the program with the results obtained from the sample of the experiment. © 2009, INSInet Publication.
Keywords: Cost calculation; Molding parameters; Plastic injection molds